Gebruikt bij culturele conferentie van AABN e.a. over Zuid-Afrika in de Balie, december 1982. Zie ook BG B32/461 - Koperdraat, Jan (1982)
Gebruikt bij culturele conferentie van AABN e.a. over Zuid-Afrika in de Balie, december 1982. Zie ook BG B32/461.